Occupational hazards and associated risks in university laboratories: A case study of mining engineering department laboratory - Al-Bakri, Ali Y.; Ahmed, Haitham M.; Hefni, Mohammed (Journal of King Abdulaziz University: Engineering Sciences, 2023)
Laboratories occupy a prominent role in the academic field through research, experimentation, and promoting educational practices for students. On the other hand, university laboratories’ work is accompanied by some risks that may negatively impact the safety of researchers, students, technical staff, and visitors. This paper, through the mining engineering lab, carried out a risk assessment from an occupational safety perspective. The conducted risk assessment aimed to identify the equipment’s potential induced hazards, review existing controls, minimize the associated risks, prioritize them, and then create a safe work area with additional control measures. The study covered sixteen significant pieces of machines in mineral processing and rock mechanics labs. Obtained results indicated around seventy-two identified hazards. A high-risforscale is assessed in the equipment of Electromagnetic and Magnetic Separators. Both required strict additional control measures as recommended. In addition, outcomes showed some medium-risk scale might be related to operating the manual drilling equipment and the crusher. The acceptable levels of risk scale have been achieved in most laboratory equipment; however, some additional control measures are suggested to reach the minimum levels of risks. The literature review revealed a significant lack of research conducted to examine the university laboratories’ risk except for labs used in the chemical studies. Therefore, more studies are strongly recommended to investigate the occupational hazards and associated risks in university laboratories.